The combined effects of Lamaze breathing training and nursing intervention on the delivery in primipara: A PRISMA systematic review meta-analysis. Issue 4 (29th January 2021) - Wu, Chao; Ge, Yiling; Zhang, Xinyan; Du, Yanling; He, Shizhe; Ji, Zhaohua; Lang, Hongjuan
Abstract: Background: Lamaze breathing has been widely used as a breathing training method. Nursing intervention including postural nursing, delivery ball, doula nursing, massage and psychological nursing is usually provided by nurses during labor. A number of clinical studies have investigated the effect of Lamaze breathing training combined with nursing intervention on maternal pain relief and outcomes improvement. But there were some scholars who were against it. Methods: Randomized controlled trials from January 2000 to November 2019 in PubMed, Cochrance Library, Medline, Web of Science, Embase, Chinese Academic Journals, Chinese Biomedical Literature Database, VIP Database, Wanfang Database were searched. Two researchers independently screened the literature according to the criteria. After extracting the data, the researchers used Cochrane system to evaluate the literature quality. Statistical analyses were performed by using Comprehensive Meta Analysis V2 software. Results: Twenty-two randomized controlled trials conducted on 7035 primiparas were eligible. The results revealed that Lamaze breathing training combined with nursing intervention increased the rate of natural delivery (relative risk [RR] = 2.97, 95% confidence interval [CI] [2.48, 3.56]), shortened the length of labor (−2.604, 95% CI [−3.120, −2.087]), alleviated labor pain (RR = 0.194, 95% CI [0.115, 0.325]) and reduced postpartum bleeding (−2.966, 95% CI [−4.056, −1.877]). Conclusions: Lamaze breathing training combined with nursing intervention was effective for ameliorating the process and outcomes of childbirth in primiparae and deserves to be promoted and applied in clinical practice.